Oxidative post‐translational modifications of plant antioxidant systems under environmental stress - Jiménez, Ana; Martí, María Carmen; Sevilla, Francisca (Physiologia plantarum, 2025)
Plants are often subject to environmental challenges posed by abiotic and biotic stresses, which are increasing under the current climate change conditions, provoking a loss in crop yield worldwide. Plants must cope with adverse situations such as increasing temperatures, air pollution or loss of agricultural land due to salinity, drought, contamination, and pathogen attacks, among others. Plants under stress conditions increase the production of reactive oxygen‐, nitrogen‐, and sulphur species (ROS/RNS/RSS), whose concentrations must be tightly regulated. The enzymatic antioxidant system and metabolites are in charge of their control to avoid their deleterious effects on cellular components, allowing their participation in signalling events. As signalling molecules, reactive species are involved in plant responses to the environment through post‐translational modifications (PTMs) of proteins, which, in turn, may regulate the structure, function, and location of the antioxidant proteins by oxidative/nitrosative/persulfure modifications of different amino acid residues. In this review, we examine the different effects of these post‐translational modifications, which are emerging as a fine‐tuned point of control of the antioxidant systems involved in plant responses to climate change, a growing threat to crop production.